'Deep in the earth a shining substance:' sequestration and display in gold mining and central banks. Issue 4 (4th July 2021) - Ferry, Elizabeth
ABSTRACT: In this essay, I consider the ways in which gold acts and is perceived as a reserve in the El Cubo mine in Guanajuato, Mexico, and in some European central banks. Following Gustav Peebles' essay 'Rehabilitating the Hoard' (2014), I consider the ways in which gold's movement from mine to vault helps to express a dialectic of sequestration and display that enables its operation as hoard, providing for struggles over sovereignty, stewardship, and the global transfer of value from South to North.